Azurin and HS–: Towards Implementation of a Sensor for HS– Detection. Issue 6 (21st January 2019) - Strianese, Maria; Palm, Gottfried J.; Kohlhause, David; Ndamba, Lionel A.; Tabares, Leandro C.; Pellecchia, Claudio
Abstract : Hydrogen sulfide (H2 S) is an important biological messenger, which recently joined nitric oxide (NO) and carbon monoxide (CO) as an endogenously produced gasotransmitter. This discovery resulted in a renewed interest towards H2 S and, in particular, in its reactivity with biological and bioinorganic targets. However, in the scientific literature studies exploring the reactivity of H2 S/HS – with non‐heme proteins are rare. In this work, we studied the interaction of HS – with the natural metalloprotein Cu‐azurin and its cobalt variant via UV‐Vis, fluorescence, and EPR spectroscopy, as well as X‐ray diffraction. Interaction of HS – significantly enhances the fluorescence emission of fluorescently labelled copper azurin in buffered solutions and at physiological pH. In contrast, fluorescently labelled cobalt azurin undergoes a fluorescence quenching in the presence of HS – in line with the changes observed in the absorption spectrum of the construct. The results highlight the potential of azurin for implementation in a fast and simple HS – sensor. Abstract : We studied the interaction of HS – with the natural metalloprotein Cu‐azurin and its cobalt variant via UV‐Vis, fluorescence, X‐ray diffraction and EPR. Interaction of HS – enhances fluorescence emission of labelled copper azurin in buffered solutions and at physiological pH. In contrast, cobalt azurin undergoes a fluorescence quenching in the presence of HS – in line with the changes observed in the absorption spectrum of the construct. The results provide proof of principle that azurin can be implemented in a fast and simple HS – sensor.